2019
DOI: 10.1111/cdev.13347
|View full text |Cite
|
Sign up to set email alerts
|

Effort Self‐Talk Benefits the Mathematics Performance of Children With Negative Competence Beliefs

Abstract: Children with negative competence beliefs often achieve below their potential in school. This randomized field experiment tested whether engaging in positive self-talk may benefit these children's mathematics performance. Participants (N = 212, Grades 4-6, M age = 10.6) worked on the first half of a standardized mathematics test, engaged in effort self-talk ("I will do my very best!"), ability self-talk ("I am very good at this!"), or no self-talk, and worked on the second half of the test. Compared to both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Growth-mindset speech Practicing noticing "fixed mindset messages" in one's internal speech and learning to change them into "growth mindset messages" (Thomaes et al, 2020) through pair discussion and drama. Students were introduced to growth-oriented inner speech with examples such as "I don't know it yet," "It feels hard now, but I can learn it" or "Everyone makes mistakes; it is a normal part of learning.…”
Section: Internal Speechmentioning
confidence: 99%
“…Growth-mindset speech Practicing noticing "fixed mindset messages" in one's internal speech and learning to change them into "growth mindset messages" (Thomaes et al, 2020) through pair discussion and drama. Students were introduced to growth-oriented inner speech with examples such as "I don't know it yet," "It feels hard now, but I can learn it" or "Everyone makes mistakes; it is a normal part of learning.…”
Section: Internal Speechmentioning
confidence: 99%
“…Positive academic self-perception or self-concept is an important prerequisite for academic achievement (Byrne & Shavelson, 1986; Febriana & Mujiyanto, 2020; Hussain et al, 2019; Thomaes et al, 2020). Academic self-perception or self-concept involves the beliefs we hold about our academic abilities, behavior, and competence (Bandura, 1993; Byrne & Shavelson, 1986; Marsh & Craven, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers found self-concept interventions using feedback, and specifically attributional feedback, goal feedback, or contingent praise, are most effective (O’Mara et al, 2006b). Furthermore, researchers found that positive self-talk is associated with higher levels of self-concept (Burnett, 1999, 2003) and that targeting positive self-talk can improve achievement for students with lower self-competence beliefs (Thomaes et al, 2020). Therefore, the AME curriculum explicitly targets self-concept and positive self-talk.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Good levels of hypertext comprehension could be a consequence of the presence of links that encouraged readers to establish high levels of interaction with texts. A typical reading behavior observed by this researcher was that the readers were involved in constant self-talk, asking questions to oneself, and metacognitive reflection, all of which helped reduce reading anxiety and aided selfimprovement (Thomaes, Tjaarda, Brummelman & Sedikides, 2019). Several instances of affirmative reader conversations were recorded such as, "This word… I can find out" (reader 27); "…okay, it is not here, but it will be coming in another place" (reader 7); "I'm not getting this…not to worry, but I know I will be getting it…let's look here then…" (reader 21).…”
Section: Discussionmentioning
confidence: 99%